Beethoven for three : [compact disc] Symphonies Nos. 2 and 5 - Beethoven, Ludwig van, 1770-1827 (Sony Classical, 2022)
Emanuel Ax, Leonidas Kavakos, and Yo-Yo Ma's new recording explores two of Beethoven's iconic symphonies in trio arrangements, maintaining all of the power and immediacy of the composer's orchestral works within the intimate language of a chamber ensemble.